Bifid epiglottis with midline laryngeal hamartoma: a rare presentation of Pallister Hall syndrome - Thirunavukkarasu, Saravanamuthu; Sandu, Kishore; Revathy, Sasikumar; Ramesh, Singaravelu; Namasivayam, Selvarajan (International Journal of Contemporary Pediatrics, 2020)
Bifid epiglottis is a rare laryngeal anomaly that can be an isolated occurrence or as part of malformation syndromes, commonly the Pallister Hall syndrome (PHS). PHS presents with hypothalamic hamartomas, polysyndactyly, bifid epiglottis, imperforate anus and genitourinary abnormalities. We report a case of a 22 months old male child with features of PHS and Hirschsprung's disease. The presentations are with a hypothalamic mass, a bifid epiglottis and a midline mass in the larynx with symptoms of respiratory distress. The laryngeal lesion was endoscopically excised and its histology confirmed as hamartoma (laryngeal). The importance of an early diagnosis of PHS, genetic counselling and prompt management of a compromised airway and endocrine abnormalities is emphasized to have a better outcome.